Management of Kedung Gede Lenteng Agung Tourism Village As an Efforts to Empower Local Communities in The Ciliwung Area - Rizki Nurul Nugraha; Vironika Agustin Saputra (West Science Social and Humanities Studies, 2024)
This research highlights the management of the Kedung Gede Lenteng Agung Tourism Village as an effort to empower local communities in the Ciliwung area, with a focus on success factors. This research aims to provide a comprehensive picture of the contribution of tourist villages in community empowerment. The urgency of the research lies in understanding how the management of the Kedung Gede Lenteng Agung Tourism Village has become an instrument for local community empowerment which has the potential to impact the local economy, preserve culture and improve welfare in the Ciliwung area. The research location is in the Kedung Gede Lenteng Agung Tourism Village, South Jakarta, as a specific context that is relevant for understanding community empowerment efforts through tourism villages. The research method uses descriptive qualitative, allowing in-depth analysis of tourism village management and its success factors. Primary data was obtained through interviews, observation and documentation, while secondary data came from literature studies which included books, journals and internet sources related to the research topic. The research results show that active community participation has a central role in the successful management of tourist villages as an effort to empower communities in the Ciliwung area.